Pengaruh Layanan Perpustakaan Terhadap Tingkat Kepuasan Siswa di SMAN 1 Taliwang - Hardiansyah, Hardiansyah; Hakim, Lukman; Faqih, Muhammad; Ariyani , Nindy Syafira (Yayasan Alpatih Harapan Semesta, 2023)
This study aims at determining: 1) the level of quality of library services at SMAN 1 Taliwang, 2) the level of student satisfaction with library services at SMAN 1 Taliwang, and 3) the effect of library services on the level of student satisfaction at SMAN 1 Taliwang. The research approach used quantitative methods with ex-post facto research types. The research sample totaling 100 students was determined by stratified random sampling technique. Data collection techniques using questionnaires and data analysis using simple regression analysis. The results showed that: 1.) Of the 3 categories of library services that students liked more, namely circulation services. The results of an analysis of Library Services showed that 39% of students gave a